Phenolic Derivatives from Meliaceae Family and Their Biological Activities - Ainazzahra, Hikma; Inayah, Citra Nisa Ul; Naini, Al Arofatus; Farabi, Kindi; Harneti, Desi; Supratman, Unang (Trends in Sciences, 2025)
Phenolic compounds are an important class of secondary metabolites found in the Meliaceae family, which is widely distributed in tropical and subtropical regions. This study presents a comprehensive review of 73 scientific publications from 1985 to 2024, focusing on the occurrence, classification, and biological activities of phenolic compounds isolated from various plant parts such as leaves, barks, seeds, roots, fruits, and flowers. A total of 147 phenolic compounds were identified, categorized into major groups including simple phenolics, coumarins, stilbenes, flavonoids, and lignans. Lignans were the most abundant class, accounting for 45.6% of the total compounds reported. These phenolic constituents exhibit a wide range of biological activities, such as antioxidant, anti-inflammatory, antimicrobial, anticancer, and agonistic activity. Notably, several lignans, such as methyl rocaglate and its derivatives, displayed potent cytotoxicity in the nanomolar range (IC₅₀ = 0.0023 - 0.068 µM), highlighting their potential as anticancer agents. Data were collected and analyzed using established scientific databases including PubMed, Scopus, Reaxys, and SciFinder. The findings underscore the rich chemical diversity and therapeutic potential of Meliaceae-derived phenolics, particularly lignans, as promising candidates for pharmaceutical development. Further pharmacological and clinical investigations are recommended to validate their efficacy and safety. HIGHLIGHTS A comprehensive review of 147 phenolic compounds from 17 genera within the Meliaceae family. Lignans are the predominant class of phenolic compounds, representing 46.3% of total isolates. Several compounds demonstrated potent antioxidant, cytotoxic, anti-inflammatory, antimicrobial, and agonistic activities. The study identifies Meliaceae-derived phenolics as promising leads for pharmaceutical and therapeutic development. GRAPHICAL ABSTRACT